Reframing austerity: financial morality, savings and securitization. Issue 4 (4th July 2017) - Bryan, Dick; Rafferty, Michael
ABSTRACT: Austerity in the twenty-first century is different, compared both with the past, and across locations. This analysis explores the different role played by households in policies designed to maintain financial market liquidity in the context of aspirations of state deficit reduction. While in Europe there is austerity as popularly depicted, in the United States, where mortgage-backed securities have become central to monetary policy, the agenda is to keep households meeting their debt obligations. These differences are explained in terms of different conceptions of monetary policy and evolving conceptions of money itself. The evidence portends a changing role for households and their financial payments in anchoring the money system.